Persepsi Kelompok Tani terhadap Peranan Penyuluh Pertanian di Kecamatan Rantau Utara Kabupaten Labuhan Batu - Siregar, Joni Rianto; Ginting, Rahmanta; Effendi, Ihsan (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
The purpose of this study is to describe Farmers Group Perceptions of the Role of Agricultural Extension Workers in the development of Farmer Groups in Rantau Utara District, Labuhanbatu Regency and find out related to extension agents in various training programs for farmer groups in Nagari Sungai Pua, Sungai Pua District, Agam District. This research is a survey research, using selected respondents using a multistage sampling method by selecting 7 out of 68 farmer groups and choosing 79 respondents from selected farmer groups, which is carried out intentionally. Data were analyzed descriptively quantitative and qualitative. The results showed that the role of instructors as motivators of educators, instructors, administrators, and communicators was categorized in participation, while the role of instructors as catalysts and consultants was categorized as not supportive. From this result it was agreed that extension agents were expected to further increase their contribution by assisting farmers in solving problems, assisting the process in the field and connecting farmers with technology sources.